Responsibility of Agro Processing Industries in Rural Development - Parashar, Amrit (Journal of Commerce and Trade, 2014)
Most important point in the agro-processing is that a sizeable portion of raw material processed in them being rural based it has a very high employment potential with significantly lower investment. Agro-industry generates new demand on the farm sector for more and different agricultural outputs, which are more suitable for processing. On the other hand, development of these industries would relax wage goods constraints to economic growth by enhancing the supply of their products. In this context there is a need for improving the capacity of the agro-industries to harness backward linkages with agriculture and allied activities in order to efficiently convert part of the output to value added products acceptable to the domestic and international markets. This would generate employment opportunities for different types of skills through food processing, packaging, grading and distribution. At the same time this will transfer a size margin to farmers through market linkages.